Theoreticals principles of stabilization and structureformation metallizied colloid solutions of poligraphic appointment - Морозов, Андрій Сергійович (Technology audit and production reserves, 2012)
The results of development and analysis of physical and mathematical models for the determination of significant parameters, which accompany the process of stabilization and polymerization metallizied paints, intended for printing process are considered on the article. Is determinated, what on the stage of manufacture the paint how colloid systems by of stabilization all its components one can regulate the process of the formation structure of polymer painted coating with metallic component